2018
DOI: 10.1073/pnas.1717720115
|View full text |Cite
|
Sign up to set email alerts
|

Humans incorporate attention-dependent uncertainty into perceptual decisions and confidence

Abstract: Perceptual decisions are better when they take uncertainty into account. Uncertainty arises not only from the properties of sensory input but also from cognitive sources, such as different levels of attention. However, it is unknown whether humans appropriately adjust for such cognitive sources of uncertainty during perceptual decision-making. Here we show that, in a task in which uncertainty is relevant for performance, human categorization and confidence decisions take into account uncertainty related to att… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
135
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(150 citation statements)
references
References 52 publications
15
135
0
Order By: Relevance
“…One could object to our critique by questioning the relevance of overlapping stimulus distributions, given that non-overlapping stimulus distributions are the norm in the confidence literature 2,17,18,37 . But although overlapping categories are only just beginning to be used to study confidence 1,7 , such categories have a long history in the perceptual categorization literature 4,13,15,23,24,35,36 . It has been argued that overlapping Gaussian stimulus distributions have several properties that make them more naturalistic than non-overlapping distributions 26 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One could object to our critique by questioning the relevance of overlapping stimulus distributions, given that non-overlapping stimulus distributions are the norm in the confidence literature 2,17,18,37 . But although overlapping categories are only just beginning to be used to study confidence 1,7 , such categories have a long history in the perceptual categorization literature 4,13,15,23,24,35,36 . It has been argued that overlapping Gaussian stimulus distributions have several properties that make them more naturalistic than non-overlapping distributions 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Second, the experimenter must determine how much evidence that provides in favor of the BCH, and whether further investigation is warranted. By contrast, model comparison provides a principled quantity (namely, a log likelihood) in favor of the BCH over some other model 1,2,7 . Given the caveats associated with qualitative signatures, it may be that, as a field, we have no choice but to rely on formal model comparison.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that these aspects can interact with attention and metacognition (Stein & Peelen, 2017;Matthews et al, 2018). In addition, the precise influence of evidence-reliability remains to be elucidated in more extensive work as it has also been shown to affect confidence judgments and metacognition (Boldt, De Gardelle & Yeung, 2017;Bang & Fleming, 2018;Denison & al., 2018).…”
Section: Limitations and Further Questionsmentioning
confidence: 99%
“…Attention and confidence have already been considered in the spatial domain, leading to mixed findings. Some studies observed a dissociation between the two (Rahnev et al, 2011(Rahnev et al, , 2012Schoenherr, Leth-Steensen, & Petrusic, 2010;Wilimzig, Tsuchiya, Fahle, Einhäuser, & Koch, 2008), while other works tend to suggest that attention-dependent spatial uncertainty is usually well incorporated into confidence (Denison, Adler, Carrasco, & Ma, 2018;Zizlsperger, Sauvigny, & Haarmeier, 2012;Zizlsperger, Sauvigny, Händel, & Haarmeier, 2014). An open question relates to temporal attention and its link to confidence.…”
Section: Introductionmentioning
confidence: 99%